Polyurethane-lipoic acid copolymer and / or its derivative thermal interface material, preparation method and use thereof
By introducing multiple hydrogen bonds, dynamic disulfide bonds and molecular chain entanglement networks into the polyurethane-liocytic acid copolymer thermal interface materials, the problem of difficulty in taking into account the high bonding performance, ultra-high fracture energy and low interface contact thermal resistance is solved, and a high-performance thermal interface material is achieved.
Patent Information
- Application Number
- CN202310185570.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-01
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2043-03-01
AI Technical Summary
It is difficult for existing thermal interface materials to take into account high bonding performance, ultra-high breaking energy and low interface contact thermal resistance, resulting in limited application in actual environments.
Design a polyurethane-lipoic acid copolymer and/or its derivative thermal interface material to improve its bonding performance, breaking energy and interface contact thermal conductivity by introducing multiple hydrogen bonds, dynamic disulfide bonds and a large number of molecular chain entanglement networks.
The high bonding performance, high fracture energy and high interface contact thermal interface material of polyurethane-lipoic acid copolymer are achieved, improving its application performance in actual environment.
Smart Images

Figure CN116217857B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer structures, and particularly relates to a polyurethane-lipoic acid copolymer and / or its derivative thermal interface material having high bonding performance, ultra-high fracture energy and low interface contact thermal resistance, a preparation method and use thereof. Background Art
[0002] With the rapid development of high-performance integrated devices in the information age, the industry has put forward higher requirements for efficient thermal management of electronic components. When the device is at the phonon mean free path scale, the impact of the interface contact thermal resistance on thermal management is higher than the intrinsic thermal conductivity of the material. Therefore, how to reduce the interface contact thermal resistance of thermal interface materials becomes an important challenge. Interface bonding performance and interface phonon matching are two important factors affecting interface contact thermal conductivity. The bonding performance of thermal interface materials can be effectively improved through interface molecular design, for example: 1) constructing strong interface interaction forces such as dynamic covalent bonds and chemical bonds; 2) introducing molecular chain entanglement network structures and filler networks in elastomers to enhance fracture energy. Good bonding performance can effectively fill the interface gaps in electronic components to achieve a shock-absorbing effect. Optimizing interface bonding and phonon matching performance can further regulate interface contact thermal conductivity, but currently it generally faces the following difficulties: 1) It is difficult to simultaneously take into account high bonding strength and high fracture energy to ensure high bonding work of thermal interface materials; 2) High bonding performance and interface phonon matching are simultaneously required to improve interface contact thermal conductivity.
[0003] Xiongwei Zhao et al. synthesized borosiloxane oligomers as a surface treatment agent for epoxy resin to construct interfacial hydrogen bonds, and the interfacial adhesion performance between epoxy resin and addition-curable liquid silicone rubber can be improved to 0.18 MPa (Zhao X, Zang C, Sun Y, et al. Borosiloxane oligomers for improving adhesion of addition-curable liquid silicone rubber with epoxy resin by surface treatment [J]. Journal of Materials Science, 2018, 53 (2): 1167-1177.); Michael G. Mazzotta et al. pointed out that epoxy resin and polyurethane-based acrylic resin polymer adhesives usually have extremely strong adhesion, but due to their own brittleness, the low bonding work caused usually leads to undesirable cohesive failure (Mazzotta MG, Putnam AA, North MA, et al. Weak bonds in a biomimetic adhesive enhance toughness and performance [J]. Journal of the American Chemical Society Society, 2020, 142(10): 4762-4768.); Jianyu Li et al. designed an adhesive with a two-layer structure of an adhesive surface and a dissipation mechanism inspired by biology. The former is attached to the substrate through electrostatic interaction, covalent bonds and physical interpenetration, and the latter dissipates energy through hysteresis amplification. The bonding force is 0.083±0.031MPa and the bonding work is up to 1116J / m 2 (Li J, Celiz AD, Yang J, et al. Tough adhesives for diverse wet surfaces [J]. Science, 2017, 357 (6349): 378-381.). However, the above work ignores the influence of material fracture energy on bonding work when regulating the bonding force, and cannot achieve high bonding force at the same time when optimizing the bonding work, which greatly limits the application of thermal interface materials in practical environments.
[0004] It has been reported that high adhesion leads to low interfacial contact thermal conductivity due to the inability to take into account the interface phonon matching. BinXu et al. constructed a copper / SH-(CH2) based on covalent bonds. 3-diamond interface and copper / CH3-(CH2)3-diamond interface based on van der Waals force. The former has stronger interface bonding performance and its interface contact thermal conductivity is 33.6MW / (m 2 ·K), the latter has weaker bonding performance, but due to its higher phonon matching, its interface contact thermal conductivity reaches 61.5MW / (m 2 ·K)(Xu B, Hu S, Hung SW, et al. Weaker bonding can give larger thermal conductance at highly mismatched interfaces[J]. Science Advances, 2021, 7(17): eabf8197.). This work proposes that when regulating the interfacial contact thermal conductivity by bonding force, the influence of interface phonon matching cannot be ignored. To this end, the present invention proposes a polyurethane-lipoic acid copolymer and / or a thermal interface material derived therefrom, which has high bonding performance and high fracture energy while having high interfacial phonon matching, and further obtains high interfacial contact thermal conductivity, which is of great practical significance for the development of the industry. Summary of the invention
[0005] In view of the technical problems existing in the above-mentioned prior art, the purpose of the present invention is to design and provide a polyurethane-lipoic acid copolymer and / or its derivative thermal interface material, a preparation method and its use. From the perspective of molecular design, the present invention introduces multiple hydrogen bonds, dynamic disulfide bonds and a large number of molecular chain entanglement networks into the synthesized polyurethane-lipoic acid copolymer and / or its derivative thermal interface material, so as to achieve high bonding performance, high fracture energy and interface contact thermal conductivity.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] In one aspect, the present invention provides a polyurethane-lipoic acid copolymer and / or its derivative thermal interface material comprising the following raw material components:
[0008] 1 to 20 parts by weight of adipic acid dihydrazide;
[0009] 1 to 20 parts by weight of isocyanate polymer;
[0010] Dimethylacetamide 1-100 parts by mass;
[0011] 1 to 20 parts by weight of formate polymers containing olefin, hydroxyl, carboxyl, epoxy or amino groups at both ends;
[0012] 1 to 1000 parts by weight of lipoic acid;
[0013] Catalyst 0.01-0.5 parts by mass.
[0014] The polyurethane-lipoic acid copolymer and / or its derivative thermal interface material, the isocyanate-based polymer includes isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, and dicyclohexylmethane diisocyanate.
[0015] The polyurethane-lipoic acid copolymer and / or its derivative thermal interface material, the formate polymer containing olefin or hydroxyl or carboxyl or epoxy or amino at both ends includes ethylene glycol monoallyl ether, acrylamide, acrylic acid, epoxybutene.
[0016] The polyurethane-lipoic acid copolymer and / or its derivative thermal interface material is characterized in that the catalyst comprises a polyurethane metal catalyst, and preferably the polyurethane metal catalyst comprises dibutyltin dilaurate, stannous isooctanoate, and zinc isooctanoate.
[0017] In a second aspect, the present invention provides a method for preparing the polyurethane-lipoic acid copolymer and / or its derivative thermal interface material, comprising the following steps:
[0018] (1) Under air atmosphere, weigh adipic acid dihydrazide, a catalyst, dimethylacetamide and an isocyanate polymer, add and mix them in sequence, and react to obtain a diacid dihydrazide-isocyanate copolymer (AD-NCO);
[0019] (2) adding a formate polymer containing olefin, hydroxyl, carboxyl, epoxy and amino groups at both ends, mixing, and reacting to obtain a formate polymer-diacid dihydrazide-isocyanate copolymer (AD-NCO-AG);
[0020] (3) Weigh lipoic acid, heat until the lipoic acid is completely dissolved, add formate polymer-diacid dihydrazide-isocyanate copolymer, react, and obtain polyurethane-lipoic acid copolymer (PU-TA).
[0021] (4) The polyurethane-lipoic acid copolymer was spin-coated on metallic aluminum to obtain the polyurethane-lipoic acid copolymer / aluminum, and the adhesion, interface contact thermal conductivity and fracture energy were measured.
[0022] In the preparation method, the mass and volume ratio of the adipic acid dihydrazide, catalyst, dimethylacetamide and isocyanate polymer in step (1) is 1g: 0.001-0.003g: 30-60mL: 10-1000g; the reaction conditions are: temperature 50-100°C, time 1-3h.
[0023] In the preparation method, in step (2), the mass to volume ratio of the formate polymer containing olefin, hydroxyl, carboxyl, epoxy and amino groups at both ends to the diacid dihydrazide-isocyanate copolymer is 5g:10-100mL; and the reaction conditions are: temperature 60-80°C, time 1-3h.
[0024] In the preparation method, the molar ratio of lipoic acid to formate polymer-diacid dihydrazide-isocyanate copolymer in step (3) is 5-1000:1; the heating conditions are: temperature 150-170°C, time 10-30min; the reaction conditions are: temperature 150-170°C, time 10-30min.
[0025] In a third aspect, the present invention provides the use of the polyurethane-lipoic acid copolymer and / or its derivative thermal interface material as a thermal interface material having high bonding performance, high fracture energy, and high interface contact thermal conductivity.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] The present invention introduces multiple hydrogen bonds, dynamic disulfide bonds and a large number of molecular chain entanglement networks into the synthesized polyurethane-lipoic acid copolymer and / or its derived thermal interface materials from the perspective of molecular design, and utilizes multiple hydrogen bonds to improve the interface adhesion (0.05-5MPa). Physical entanglement can be used to achieve ultra-high fracture energy (5-250mJ / m 2 ), and then obtain high bonding work (600-2500J / m 2 ). Dynamic disulfide bonds are used to improve the phonon matching degree between the metal matrix and ultimately achieve high interfacial contact thermal conductivity (50-250MW / (m 2 ·K)). BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a structural diagram of the thermal interface material of the present invention;
[0029] Figure 2 This is a process flow chart of the thermal interface material of the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0031] Embodiment 1:
[0032] (1) Synthesis of adipic acid dihydrazide-isophorone diisocyanate (AD-NCO): In an air atmosphere, 4.355 g of adipic acid dihydrazide, 0.0774 g of dibutyltin dilaurate, 30 ml of dimethylacetamide and 11.114 g of isophorone diisocyanate were added and mixed in sequence, and reacted at 70° C. for 2 h to obtain adipic acid dihydrazide-isophorone diisocyanate (AD-NCO). Reaction formula I is as follows:
[0033]
[0034] (2) Synthesis of adipic acid dihydrazide-isophorone diisocyanate-ethylene glycol monoallyl ether (AD-NCO-AG): The AD-NCO in (1) was mixed with 5.107 g of ethylene glycol monoallyl ether and 10 ml of dimethylacetamide, and reacted at 70° C. for 2 h to obtain adipic acid dihydrazide-isophorone diisocyanate-ethylene glycol monoallyl ether (AD-NCO-AG). Reaction formula II is as follows:
[0035]
[0036] (3) Synthesis of polyurethane-lipoic acid copolymer: 10 g of lipoic acid was heated at 160° C. for 20 min. When the lipoic acid was completely dissolved, 0.0845 g of AD-NCO-AG in (2) was added according to the molar ratio of lipoic acid to AD-NCO-AG being 500:1, and the mixture was reacted at 160° C. for 20 min to obtain a polyurethane-lipoic acid copolymer. The product was named PU-TA@500-1. Reaction formula III is as follows: Figure 1 This is a structural diagram of the thermal interface material of the present invention; Figure 2 This is a process flow chart of the thermal interface material of the present invention.
[0037]
[0038] (4) Synthesis of polyurethane-thioctic acid copolymer / metal aluminum (PU-TA / Al): A 46±1 nm thick aluminum layer was evaporated on a 200 μm thick quartz glass by physical vapor deposition technology. The molten polyurethane-thioctic acid copolymer in (3) was evenly spin-coated on the aluminum layer at a speed of 400 rpm and cured at 80°C for 12 h to obtain a polyurethane-thioctic acid copolymer / metal aluminum model interface for femtosecond laser pumping thermal reflection method measurement; the cured polyurethane-thioctic acid copolymer was placed between two aluminum layers with a thickness of 300 μm for interfacial adhesion measurement; the cured polyurethane-thioctic acid copolymer was cut into rectangular specimens with a length of 20 mm, a width of 10 mm, and a thickness of 2 mm, and a "V"-shaped notch rectangular specimen with a length of 20 mm, a width of 10 mm, a thickness of 2 mm, and a depth of 2 mm for fracture energy testing.
[0039] Embodiment 2:
[0040] The method was the same as that in Example 1 except that the step (3) of "adding 0.0845 g of AD-NCO-AG from (2) at a molar ratio of thioctic acid to AD-NCO-AG of 500:1" was replaced by adding 0.106 g of AD-NCO-AG from (2) at a molar ratio of thioctic acid to AD-NCO-AG of 400:1. The obtained product was named PU-TA@400-1.
[0041] Embodiment 3:
[0042] The method was the same as that in Example 1 except that in step (3) of Example 1, "adding 0.0845 g of AD-NCO-AG from (2) at a molar ratio of thioctic acid to AD-NCO-AG of 500:1" was replaced by adding 0.141 g of AD-NCO-AG from (2) at a molar ratio of thioctic acid to AD-NCO-AG of 300:1. The product was named PU-TA@300-1.
[0043] Embodiment 4:
[0044] The method was the same as that in Example 1 except that in step (3) of Example 1, "adding 0.0845 g of AD-NCO-AG from (2) at a molar ratio of thioctic acid to AD-NCO-AG of 500:1" was replaced by adding 0.212 g of AD-NCO-AG from (2) at a molar ratio of thioctic acid to AD-NCO-AG of 200:1. The product was named PU-TA@200-1.
[0045] Embodiment 5:
[0046] The method was the same as that in Example 1 except that in step (3) of Example 1, "adding 0.0845 g of AD-NCO-AG from (2) at a molar ratio of thioctic acid to AD-NCO-AG of 500:1" was replaced by adding 0.423 g of AD-NCO-AG from (2) at a molar ratio of thioctic acid to AD-NCO-AG of 100:1. The product was named PU-TA@100-1.
[0047] Embodiment 6:
[0048] Except that in step (3) of Example 1, "according to the molar ratio of thioctic acid to AD-NCO-AG of 500:1, 0.0845g AD-NCO-AG from (2) is added" is replaced by "according to the molar ratio of thioctic acid to AD-NCO-AG of 15:1, 2.818g AD-NCO-AG from (2) is added", the rest is the same as Example 1, and the product is named PU-TA@15-1.
[0049] Comparative Example 1:
[0050] (1) The prepolymer component A and the prepolymer component B of commercial Dow Corning 184 were mixed in a mass ratio of 10:1, and the mixture was stirred at 8000 rpm for 5 minutes under normal pressure and room temperature to react and obtain liquid silicone.
[0051] (2) Synthesis of organosilicon / metal aluminum (PDMS / Al): A 46±1 nm thick aluminum layer was evaporated on a 200 μm thick quartz glass by physical vapor deposition technology. The liquid organosilicon in (1) was evenly spin-coated on the aluminum layer at a speed of 400 rpm and cured at 125°C for 1 h and then at 145°C for 3 h to obtain an organosilicon / metal aluminum model interface for femtosecond laser pumping thermal reflection method measurement. The cured organosilicon was placed between two aluminum layers with a thickness of 300 μm for interface adhesion measurement.
[0052] Comparative Example 2:
[0053] (1) Commercial bisphenol A type CYD-128 and NN dimethylbenzylamine were mixed in a mass fraction of 10:1, and 0.5% of methyl hexahydrobenzene was added to react at a speed of 8000 rpm and stirred for 5 minutes under normal pressure and room temperature to obtain a liquid epoxy resin.
[0054] (2) Epoxy resin / metal aluminum (EP / Al) synthesis: A 46±1 nm thick aluminum layer was evaporated on a 200 μm thick quartz glass by physical vapor deposition technology. The liquid epoxy resin in (1) was evenly spin-coated on the aluminum layer at a speed of 400 rpm and cured at 125°C for 1 h and then at 145°C for 3 h to obtain an epoxy resin / metal aluminum model interface for femtosecond laser pumping thermal reflection method measurement; the cured epoxy resin was placed between two aluminum layers with a thickness of 300 μm for interface adhesion measurement.
[0055] Test method:
[0056] (1) Interface contact thermal conductivity test:
[0057] The interface contact thermal conductivity is measured by a femtosecond laser pumping detector. In this test device, a femtosecond laser oscillator is used as the laser light source to emit a laser beam with a wavelength of 1030nm. A 1 / 2 optical isolator is installed at its exit to suppress the laser beam from reflecting onto the femtosecond laser oscillator. The laser beam is then split into pump light and probe light by a polarization beam splitter. The pump light passes through an electro-optic modulator and its frequency is controlled within the frequency range of 1–10MHz. The direction of the pump light is adjusted by a frequency doubling crystal between the polarization beam splitter and the electro-optic modulator. Finally, it is directed to the sample through an objective lens to heat the sample. Before the probe light is directed to the sample through the same objective lens, it is delayed by a mechanical delay stage. The reflected probe light is collected by a charge coupler, which converts the optical signal into an electrical signal. The surface temperature of the sample is further obtained as a function of time. A suitable heat transfer model is selected to fit the curve and obtain the thermophysical parameters of the sample, thereby studying the transport mechanism.
[0058] In this patent, the multilayer heat conduction model is selected for the test of the interface contact thermal conductivity of the sample. The tested sample consists of a three-layer structure, namely, quartz glass (Si), sensing layer aluminum (Al) and polymer (PU-TA). In order to calculate the interface contact thermal conductivity between the polymer and the metal, the thermal conductivity, specific heat and thickness of quartz glass, aluminum, polyurethane-lipoic acid copolymer, silicone (PDMS), and epoxy resin (EP) are taken as known parameters and brought into the multilayer heat transfer model for fitting. At the same time, the interface contact thermal resistance between aluminum and silicon (59.5MW / (m 2 ·K).) are also taken as known parameters and fitted into the multilayer heat transfer model. The values of each parameter are shown in Table 1.
[0059] Table 1 Thermal conductivity, specific heat and thickness values of each component in the multilayer heat transfer model
[0060]
[0061]
[0062] (2) Adhesion test
[0063] The adhesion of polyurethane-lipoic acid copolymer, silicone and epoxy resin was tested using Shimadzu universal electronic testing machine AGX-10kNVD. Test conditions and parameters: temperature 25°C, stretching speed 10mm / min. Test steps: Stretch two aluminum sheets sandwiching polyurethane-lipoic acid copolymer, record the load force and displacement during the stretching process, the highest load force point is the bonding force, and the integral of load force and displacement is the bonding work.
[0064] (3) Fracture energy test
[0065] The fracture energy of polyurethane-lipoic acid copolymer was tested using Shimadzu universal electronic testing machine AGX-10kNVD. The test conditions and parameters were as follows: temperature was 25°C and tensile speed was 10 mm / min. The tensile properties of polyurethane-lipoic acid copolymer samples without notch and with notch were tested respectively, and the stress-strain curves of the two shapes of samples were recorded respectively. The fracture energy (Γ) was calculated by the formula: The elongation at break of the notched sample is λ, and the elongation at break of the unnotched sample is λ c , the stress-strain curve of the unnotched sample is from 0 to λ c The product is obtained to obtain the toughness W of the unnotched sample, and c is the notch width of the notched sample 2mm.
[0066] Examples 1 to 6 mainly involve the influence of hydrogen bond density, and Comparative Examples 1 to 2 mainly involve the influence of the absence of hydrogen bonds.
[0067] The results of testing the adhesion, adhesion work and interface contact thermal conductivity of the thermal interface materials provided in Examples 1 to 6 and Comparative Examples 1 to 2 according to the above method are shown in Table 2:
[0068] Table 2 Adhesion force, adhesion work and interface contact thermal conductivity of the products obtained in Examples 1-6 and Comparative Examples 1-2
[0069] Adhesion strength(KPa) <![CDATA[Adhesion work (J / m 2 )]]> <![CDATA[Interface thermal conductance (MW / (m 2 ·K))]]> Example 1 88±6 821±22 53±6 Example 2 91±20 991±80 58±9 Example 3 113±9 903±71 81±6 Example 4 117±8 692±116 84±6 Example 5 128±11 777±19 90±9 Example 6 231±52 1707±59 100±10 Comparative Example 1 185±43 54±3 21±5 Comparative Example 2 1591±169 532±40 42±10
[0070] The fracture energy of Examples 1 to 6 tested according to the above method is shown in Table 3:
[0071] Table 3 Fracture energy of the products obtained in Examples 1-6
[0072] <![CDATA[Fracture energy (mJ / m 2 )]]> Example 1 59.4 Example 2 116.0 Example 3 154.3 Example 4 232.1 Example 5 23.2 Example 6 6.9
[0073] The applicant declares that the present invention illustrates the polyurethane-lipoic acid copolymer and the process for preparing the same by the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A polyurethane-lipoic acid copolymer thermal interface material, characterized in that: Contains the following raw materials: 1 to 20 parts by weight of adipic acid dihydrazide; 1 to 20 parts by weight of isocyanate; 1-100 parts by mass of dimethylacetamide; 1 to 20 parts by weight of modifier; 1 to 1000 parts by weight of lipoic acid; Catalyst 0.01-0.5 parts by mass; The isocyanate is isophorone diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate or dicyclohexylmethane diisocyanate; The modifier is ethylene glycol monoallyl ether, acrylamide, acrylic acid or epoxybutene.
2. The polyurethane-lipoic acid copolymer thermal interface material according to claim 1, characterized in that: The catalyst includes a polyurethane metal catalyst.
3. The polyurethane-lipoic acid copolymer thermal interface material according to claim 2, characterized in that: The polyurethane metal catalyst includes dibutyltin dilaurate, stannous isooctanoate and zinc isooctanoate.
4. The method for preparing the polyurethane-lipoic acid copolymer thermal interface material according to claim 1, characterized in that: The following steps are involved: (1) Under air atmosphere, weigh adipic acid dihydrazide, a catalyst, dimethylacetamide and isocyanate, add and mix in sequence, and react to obtain diacid dihydrazide-isocyanate; (2) adding a modifier, mixing, and reacting to obtain a modifier-diacid dihydrazide-isocyanate; (3) Weigh thioctic acid, heat until the thioctic acid is completely dissolved, add a modifier-diacid dihydrazide-isocyanate, react, and obtain a polyurethane-thioctic acid copolymer.
5. The preparation method according to claim 4, characterized in that: The reaction conditions in step (1) are: temperature 50-100° C., time 1-3 h.
6. The preparation method according to claim 4, characterized in that: The mass and volume ratio of the modifier to the diacid dihydrazide-isocyanate in step (2) is 5g:10-100mL; the reaction conditions are: temperature 60-80°C, time 1-3h.
7. The preparation method according to claim 4, characterized in that: The molar ratio of lipoic acid to modifier-diacid dihydrazide-isocyanate in step (3) is 5-1000:1; the heating conditions are: temperature 150-170° C., time 10-30 min; the reaction conditions are: temperature 150-170° C., time 10-30 min.
8. Use of the polyurethane-lipoic acid copolymer thermal interface material according to any one of claims 1 to 3 as a thermal interface material having high bonding performance, high fracture energy, and high interface contact thermal conductivity.
Citation Information
Patent Citations
Intrinsic self-repairing thermally conductive macromolecular polymer based on lipoic acid or / and derivative thereof, method for preparing same, and use thereof
WO2023185076A1